Phosphodiesterase 4A confers resistance to PGE2‐mediated suppression in CD25+/CD54+ NK cells. (22nd January 2021) - Chen, Ziqing; Yang, Ying; Neo, Shi Y; Shi, Hao; Chen, Yi; Wagner, Arnika K; Larsson, Karin; Tong, Le; Jakobsson, Per‐Johan; Alici, Evren; Wu, Jing; Cao, Yihai; et al.
Abstract: Inadequate persistence of tumor‐infiltrating natural killer (NK) cells is associated with poor prognosis in cancer patients. The solid tumor microenvironment is characterized by the presence of immunosuppressive factors, including prostaglandin E2 (PGE2), that limit NK cell persistence. Here, we investigate if the modulation of the cytokine environment in lung cancer with IL‐2 or IL‐15 renders NK cells resistant to suppression by PGE2. Analyzing Cancer Genome Atlas (TCGA) data, we found that high NK cell gene signatures correlate with significantly improved overall survival in patients with high levels of the prostaglandin E synthase (PTGES). In vitro, IL‐15, in contrast to IL‐2, enriches for CD25 + /CD54 + NK cells with superior mTOR activity and increased expression of the cAMP hydrolyzing enzyme phosphodiesterase 4A (PDE4A). Consequently, this distinct population of NK cells maintains their function in the presence of PGE2 and shows an increased ability to infiltrate lung adenocarcinoma tumors in vitro and in vivo . Thus, strategies to enrich CD25 + /CD54 + NK cells for adoptive cell therapy should be considered. SYNOPSIS: IL‐15 promotes a subset of NK cells that resist PGE2‐mediated suppression by mTOR‐dependent upregulation of PDE4A. Selective expansion of CD25 + CD54 + NK cells for adoptive cell therapy may be used to target tumors with high PGE2 levels. IL‐15 activates mTOR‐dependent upregulation of PDE4A in CD25 + CD54 + NK cells to resist suppression by PGE2. CD25 + CD54 + NK cells are superior in forming cell clusters and have higher anti‐tumor activity in a zebrafish xenograft model. CD25 + CD54 + NK cells efficiently infiltrate human lung adenocarcinoma spheroids. High NK cell gene signatures correlate with survival in lung adenocarcinoma patients with high prostaglandin E synthase. Abstract : IL‐15 promotes a subset of NK cells that resist PGE2‐mediated suppression by mTOR‐dependent upregulation of PDE4A. Selective expansion of CD25 + CD54 + NK cells for adoptive cell therapy may be used to target tumors with high PGE2 levels